Bioactivity of Red Leaf Extract of Pucuk Merah Plant (Syzygium myrtifolium Walp.) - Suryati; Santoni, Adlis; Arifin, Bustanul; Aisya, Nurul; Frisky, Sintia; Aisyah, Siti (Jurnal Riset Kimia, 2025)
Syzygium myrtifolium Walp. is an ornamental plant traditionally used as an herbal medicine. Ethanol extract of Syzygium myrtifolium Walp. has been reported to have activities as an antioxidant, anticancer, and antimicrobial. In this study, Syzygium myrtifolium Walp is extracted. Leaves were carried out using a multistage maceration method using methanol, ethyl acetate, and hexane solvents. Antioxidant, antimicrobial, and toxicity tests were performed, and secondary metabolite compounds, total flavonoid content, and total phenolic content were identified on red leaf extract. Total phenolic content was tested using the Folin-Ciocalteau reagent, total flavonoids with the AlCl3 reagent, antioxidants with the DPPH method, antimicrobial using the disc diffusion method, and toxicity tested using the BSLT method. The result showed that Syzygium myrtifolium Walp. Red leaf extract contained a secondary metabolite of triterpenoids, steroids, phenolics, flavonoids, alkaloids, and coumarins. The ethyl acetate and methanol extract's total phenolic and flavonoid content were 311.0520 and 420.360 mg GAE/g extract and 211.788 and 105.360 mg QE/g extract. Antioxidant activity of ethyl acetate and methanol showed that the extracts were highly antioxidant with IC50 of 19.606 and 12.0656 mg/L. The antimicrobial activity showed that the hexane extract was resistant to the bacteria Staphylococcus aureus and Propionibacterium acnes and the fungus Candida albicans. However, no inhibition zones were produced for Pseudomonas aerigunosa and Escherichia coli bacteria. The toxicity test showed that the hexane and ethyl acetate extract had strong toxic properties with LC50 of 56.65 and 16.79 mg/L, and the methanol extract was toxic with LC50 of 224.2846 mg/L.